Super immunity : the essential nutrition guide for boosting your body's defenses to live longer, stronger, and disease free - Fuhrman, Joel (HarperOne, 2011)
"Every year in September the spectre of cold and flu season arrives. It has become a fact of life. We might as well allot for our sick days knowing that we will be hit at least once, if not two to three times before Spring's arrival. In every office and in every family, there are those who get sick regularly and those who manage to stay healthy through it all. In Super Immunity, Dr. Fuhrman will explain why some of us get sick more regularly than others and offer a proven program to stay healthy through the year. Dr. Fuhrman argues that our current approach to disease is doing far more harm than good. He asserts that flu shots, antibiotics, supplements and alternative treatments are not the answer and can actually make us more sick. He explains why our current efforts are failing us. The truth is far too many have depleted or compromised immune systems. This is no surprise given antibiotics are prescribed with every cough and sniffle and it is too easy to get simply stuck in a vicious cycle of a cold or flu that passes from one family or office member to the next before you have a chance to get healthy again. The answer, he suggests, is as simple as what we eat. Super Immunity offers a detailed, proven and easy-to-follow program for escaping the sick bug and returning us to health and well-being. There is no need to dread the first Fall day, cringe at the first back to school sniffle, or call your doctor and schedule that flu shot. Super Immunity is a medical break-through that will work for you. Isn't it time you became the one who stays healthy during flu season?"--